2017
DOI: 10.3892/etm.2017.4192
|View full text |Cite
|
Sign up to set email alerts
|

Pravastatin reduces radiation-induced damage in normal tissues

Abstract: Pravastatin is an inhibitor of 3-hydroxy-3-methyl- glutaryl-coenzyme A reductase that has been reported to have therapeutic applications in a range of inflammatory conditions. The aim of the present study was to assess the radioprotective effects of pravastatin in an experimental animal model. Mice were divided into two groups: The control group received ionizing radiation with no prior medication, while the pravastatin group received pravastatin prior to ionizing radiation. Pravastatin was administered orally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 36 publications
(39 reference statements)
1
15
0
Order By: Relevance
“…Zang et al further confirmed through experiments that atorvastatin can reduce radiation-induced myocardial fibrosis by inhibiting multiple inflammatory responses and OS pathway activation 104. Doi et al showed that pravastatin could also protect tissue damage caused by radiation by reducing DNA double-strand breakage in normal tissue cells 113. However, it has been reported that atorvastatin can improve the repair of oxidative DNA damage in vascular smooth muscle cells (VSMCs) without affecting the initial level of DNA damage114.…”
Section: Drugs Therapy Of Rihdmentioning
confidence: 98%
“…Zang et al further confirmed through experiments that atorvastatin can reduce radiation-induced myocardial fibrosis by inhibiting multiple inflammatory responses and OS pathway activation 104. Doi et al showed that pravastatin could also protect tissue damage caused by radiation by reducing DNA double-strand breakage in normal tissue cells 113. However, it has been reported that atorvastatin can improve the repair of oxidative DNA damage in vascular smooth muscle cells (VSMCs) without affecting the initial level of DNA damage114.…”
Section: Drugs Therapy Of Rihdmentioning
confidence: 98%
“…GT3 and simvastin provide synergic protection against radiation-induced lethality, hematopoietic and bone marrow injury compared to the single treatments [ 196 ]. Pravastatin [ 300 ] and atorvastatin [ 301 ] have also shown radiomitigative efficacy.…”
Section: Medical Countermeasuresmentioning
confidence: 99%
“…In animal and cell culture models, statins ameliorated radiation-induced inflammation and fibrosis in different tissues [ 153 , 154 , 155 ]. When their effect on the heart and blood vessels was specifically assessed, atorvastatin ameliorated radiation-induced cardiac fibrosis, prevented vascular damage, reduced endothelial cell apoptosis, and promoted the healing of the radioactive injuries [ 124 , 156 , 157 ].…”
Section: Radiotherapymentioning
confidence: 99%